2014
DOI: 10.1016/j.ijrefrig.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of power ultrasound on ice nucleation of radish cylinders during ultrasound-assisted immersion freezing

Abstract: a b s t r a c tThe effect of ultrasound-assisted immersion freezing on the dynamic nucleation of ice and the delay from ultrasound application onset to nucleation commencement of radish cylinder samples were studied. The samples were frozen in 30% (w v À1 ) CaCl 2 solution (À20 C) in an ultrasonic bath system. To evaluate nucleation, ultrasound irradiation (20 kHz) was carried out with different durations (0 s, 3 s, 7 s, 10 s or 15 s), onset temperature (À0.5, À1, À1.5 and À2 C) and intensities (0.09, 0.17, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Also, radish was studied by Xu and others (), they investigated the 3 parameters: onset temperature, ultrasonic duration time, and ultrasonic intensity to achieve an optimum treatment for radish cylinders. The results showed that, the optimal ultrasonic condition is to onset the ultrasound of 0.26 W/ cm 2 at −0.5 °C with the duration of 7 s.…”
Section: Supercooled Crystallization Assisted By Power Ultrasoundmentioning
confidence: 99%
“…Also, radish was studied by Xu and others (), they investigated the 3 parameters: onset temperature, ultrasonic duration time, and ultrasonic intensity to achieve an optimum treatment for radish cylinders. The results showed that, the optimal ultrasonic condition is to onset the ultrasound of 0.26 W/ cm 2 at −0.5 °C with the duration of 7 s.…”
Section: Supercooled Crystallization Assisted By Power Ultrasoundmentioning
confidence: 99%
“…The parameters of ultrasound irradiation for UAF and UAFC were as follows: the frequency of 20 kHz, the duty cycle of 10 s on/10 s off, and the intensity of 0.17 W/cm 2 . The ultrasonic intensity was measured by the calorimetric method as suggested by Xu et al (2014) and calculated by the following equation.…”
Section: Freezing Proceduresmentioning
confidence: 99%
“…As we all know, the quality of frozen products is strongly related to the phase transition stage of the freezing process (Kiani, Zhang, & Sun, 2013). During this stage, the formation of ice nuclei (nucleation) and subsequent crystal growth take place (Xu, Zhang, Bhandari, & Cheng, 2014). In addition, the final product quality largely depends on the crystals' size and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Several novel quick‐freezing technologies, such as high‐pressure freezing, dehydrofreezing, and ultrasound‐assisted freezing (UAF), have been independently investigated (Cheng, Zhang, Adhikari, et al, ; Hozumi, Saito, Okawa, et al, ; Islam, Zhang, Adhikari, et al, ; LeBail, Chevalier, Mussa, et al, ; Sanz, Otero, et al, ; Xin, Zhang, & Adhikari, ; Xin, Zhang, Xu, et al, ; Xu, Zhang, Bhandari, et al, ). High‐pressure freezing promotes instantaneous and homogeneous ice nucleation in fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%